Smart contracts: um estudo da sua adoção nos países da América do Sul - Micheviz, Rafael (2024)
This dissertation investigated the adoption of smart contracts in South American countries, covering the analysis of regulatory initiatives, judicial decisions, government actions and use by private companies. After bibliographical and documentary research, in which priority was given to the analysis of official websites of the governments of the countries investigated, it was identified that the adoption of smart contracts occurred in a simpler and more objective way. Analyzing the data collected, it was identified that the creation of the electronic certificates law, which gave legal validity to virtual signatures, was a determining factor in the adoption of smart contracts. With this legislation, the courts began to apply the same rules as traditional contracts. In this context of legal recognition, several companies were established to facilitate the use and application of these technologies in the market. These companies have played a crucial role in simplifying processes and increasing efficiency in both public and private management. The research demonstrates how smart contracts have the potential to transform business and government practices in South America, highlighting the advantages of their adoption in terms of transparency, security and efficiency.